ФАРМАКОПЕЯ КАК ОСНОВА ДЛЯ ДАЛЬНЕЙШЕГО ПОВЫШЕНИЯ КАЧЕСТВА ЛЕКАРСТВЕННЫХ СРЕДСТВ В УЗБЕКИСТАНЕ (Multidisciplinary Journal of Science and Technology, 2023)
In the article, the author analyzes the organization of the development, approval and implementation of the State Pharmacopoeia in European countries, as well as the Republic of Uzbekistan in the pharmaceutical industry.